Predictors of Survival and Recurrence in Primary Leiomyosarcoma - Gladdy, Rebecca A.; Qin, Li-Xuan; Moraco, Nicole; Agaram, Narasimhan P.; Brennan, Murray F.; Singer, Samuel (Annals of surgical oncology, 2013)
Background Leiomyosarcoma is a soft tissue sarcoma whose outcome has historically been confounded by the inclusion of gastrointestinal stromal tumors. Thus, we sought to determine the factors that predict survival and recurrence in patients with primary leiomyosarcoma alone. Methods During 1982–2006, a total of 353 patients with primary resectable leiomyosarcoma were identified from a prospective database. Multivariate analysis was used to assess clinicopathologic factors for association with disease-specific survival (DSS). Competing risk survival analysis was used to determine factors predictive for local and distant recurrence. Results Of 353 patients, 170 (48 %) presented with extremity, 144 (41 %) with abdominal/retroperitoneal, and 39 (11 %) with truncal tumors. Median age was 57 (range, 18–88) years, and median follow-up was 50 (range, 1–270) months. Most tumors were high grade (75 %), deep (73 %), and completely resected (97 %); median size was 6.0 (range, 0.3–45) cm. Abdominal/retroperitoneal location was associated with worse long-term DSS compared to extremity or trunk ( P = 0.005). However, by multivariate analysis, only high grade and size were significant independent predictors of DSS. Overall, 139 patients (39 %) had recurrence: 51 % of those with abdominal/retroperitoneal, 33 % of extremity, and 26 % of truncal disease. Significant independent predictors for local recurrence were size and margin, whereas predictors for distant recurrence were size and grade. Site was not an independent predictor of recurrence; however, late recurrence (>5 years) occurred in 9 % of abdominal/retroperitoneal and 4 % of extremity lesions. Conclusions Grade and size are significant independent predictors of DSS and distant recurrence. Long-term follow-up in leiomyosarcoma is important, as late recurrence continues in 6–9 % patients.